Risk-based approach in external migration public management - V. A. Volokh; T. N. Dmitrieva (Управление)
The presence of risks emergence problem of socio-political conflict, threats to the preservation of Russian identity in the process of including foreign cultural groups of international migrants in Russian society is a consequence of public administration insufficient efficiency when implementing state migration and national policy. Applying the structural-functional method, the authors study public administration in the external migration sphere for compliance with its essential characteristics. The predominant focus of state management in the migration sphere on ensuring the human resources component of the Russian labor market, as well as on control over migration flows is combined with the state management model shortcomings in the sphere of migrants’ inclusion in the host community. External migration state management should be aimed at solving the socio-economic development problems in Russia and ensuring national security and at the same time should minimize potential risks of social and cultural nature. The authors propose a risk-oriented approach in the migration processes state management, based on a comprehensive consideration of tensions that arise both in the labor market of foreign workers and the foreigners’ inclusion in the Russian society. In order to implement the proposed method, it is advisable to define a single subject of state management, which will be able to exercise authority considering the migration process integrity.